2022
DOI: 10.1177/00033197221098277
|View full text |Cite
|
Sign up to set email alerts
|

CRP Albumin Ratio May Predict No Reflow in Patients Undergoing Percutaneous Coronary Intervention for Saphenous Vein Graft Stenosis

Abstract: Many hypotheses have been proposed to explain no-reflow (NR). Some of these hypotheses, state that NR may be caused by damage to the vascular endothelium and an inflammatory process. In a recent study that did not include patients with coronary artery bypass graft (CABG), the ratio of C-reactive protein (CRP) to albumin (CAR) was found to be associated with NR. Our study aims to evaluate the relationship between CAR and NR in patients who underwent percutaneous coronary intervention (PCI) for saphenous vein gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…24 In a recent study, Kanal et al reported that CAR was an independent predictor of the no-reflow phenomenon in patients undergoing saphenous vein graft PCI. 25 In patients with NSTEMI, complete occlusion of the responsible coronary artery is not uncommon. A study found that 22.4% of patients with NSTEMI had complete occlusion of the responsible artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In a recent study, Kanal et al reported that CAR was an independent predictor of the no-reflow phenomenon in patients undergoing saphenous vein graft PCI. 25 In patients with NSTEMI, complete occlusion of the responsible coronary artery is not uncommon. A study found that 22.4% of patients with NSTEMI had complete occlusion of the responsible artery.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a recent study, Kanal et al reported that CAR was an independent predictor of the no-reflow phenomenon in patients undergoing saphenous vein graft PCI. 25…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, nonetheless, that a wide variety of demographic, laboratory, and procedural factors have been proven to influence the development of NR. [20][21][22][23][24] Several studies have shown a link between AF-related stroke risk scoring systems, which are often used in cardiology, and NR in acute MI patients. Independent of AF and stroke risks, the impact of stroke risk scoring system components on coronary artery events was also examined.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, nonetheless, that a wide variety of demographic, laboratory, and procedural factors have been proven to influence the development of NR. 2024…”
Section: Discussionmentioning
confidence: 99%